Tourette’s Syndrome; Is there a causal link to Violence? - Yaqub, Mehboob; Akbar, Yasir; Bangar, Santosh (International Journal of Endorsing Health Science Research, 2016)
A narrative review of current literature was carried out to see whether Tourette’s syndrome is a cause of violence among patients. Two internet based resources were searched and seventeen eligible original studies were included in the review. Majority of the studies demonstrated that Tourette’s syndrome on its own does not cause violence but instead co-morbid conditions like Attention deficit hyperactivity disorder (ADHD) increased the likelihood of violence in patients directed towards self and others.